Conceptualisation of Virtual Reality Experiments for Optimised Sinus Surgery Planning and Execution - Kunica, Zoran; Poje, Gorazd; Mlivić, Denis; Topolnjak, Jan (International Journal of Industrial Engineering and Management, 2023)
Technology development allows the design and standardization of manual work in human activities which are yet to be observed, especially those of low-volume discrete production, such as in ear, nose and throat (ENT) surgery, particularly endoscopic sinus surgery (ESS). The paper considers the possibilities of developing an approach that would be useful for specific ESS manual work analysis and design and its automation in a future. The consideration includes, beside other aspects, initial steps, such as the traditional work motion capture by camera and experiments by Leap Motion Controller, Perception Neuron 2.0 and Emotiv Epoc+. Article history: Received (September 4, 2022); Revised (January 30, 2023); Accepted (February 13, 2023); Published online (February 13, 2023)